2020
DOI: 10.1097/ccm.0000000000004386
|View full text |Cite
|
Sign up to set email alerts
|

Potential for Lung Recruitment and Ventilation-Perfusion Mismatch in Patients With the Acute Respiratory Distress Syndrome From Coronavirus Disease 2019*

Abstract: Objectives: Severe cases of coronavirus disease 2019 develop the acute respiratory distress syndrome, requiring admission to the ICU. This study aimed to describe specific pathophysiological characteristics of acute respiratory distress syndrome from coronavirus disease 2019. Design: Prospective crossover physiologic study. Setting: ICU of a university-affiliated hospital from northern Italy dedicated to care of patients with confirmed diagnosis of coronavirus disease 2019. Patients: Ten intubated patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
205
1
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(235 citation statements)
references
References 27 publications
24
205
1
5
Order By: Relevance
“…The present small cases series is the first to describe early and complete respiratory mechanics evaluation in SARS-Cov-2-associated ARDS consistent with the "2 phenotypes" model proposed by Gattinoni et al [16]. Our observations extend those initially reported in three small cases series showing essentially low or variable potentials of recruitment with PEEP [4][5][6]. In the recently reported Chinese series of 12 SARS-Cov-2-associated ARDS, all patients were initially considered as poorly recruitable based on the same method to measure R/I ratio [4].…”
Section: Data Are Presented As Median [Interquartile Range]supporting
confidence: 90%
See 2 more Smart Citations
“…The present small cases series is the first to describe early and complete respiratory mechanics evaluation in SARS-Cov-2-associated ARDS consistent with the "2 phenotypes" model proposed by Gattinoni et al [16]. Our observations extend those initially reported in three small cases series showing essentially low or variable potentials of recruitment with PEEP [4][5][6]. In the recently reported Chinese series of 12 SARS-Cov-2-associated ARDS, all patients were initially considered as poorly recruitable based on the same method to measure R/I ratio [4].…”
Section: Data Are Presented As Median [Interquartile Range]supporting
confidence: 90%
“…Authors concluded that R/I ratio is feasible, even in the constrained Covid-19 environment and may allow to guide individual titration of PEEP to limit potential harmful effects expected with high PEEP in poorly recruitable patients. Most (75%) of these patients received NIV or HFNC before intubation for a median of 5 [IQR, [4][5][6][7] days. This could lead to patient self-inflicted lung injury [17] that may explain, at least in part, their low respiratory system compliance (around 20 mL/cmH 2 O) after intubation.…”
Section: Data Are Presented As Median [Interquartile Range]mentioning
confidence: 99%
See 1 more Smart Citation
“…[27][28][29] Indeed, there is increasing evidence that thrombotic phenomena in patients with severe COVID-19 can involve the pulmonary and systemic arteries, leading to a severe ventilation-perfusion mismatch in the lungs and peripheral ischaemic events. 30,31 The mechanisms involved in the inflammatory and/or virus-induced endothelial cell dysfunction and in the increase in the density of alveolar megakaryocytes in COVID- 19 patients have yet to be determined. Previous studies have demonstrated that functional Toll-like receptor 3 is expressed in megakaryocytes and platelets, suggesting a role for this receptor in the megakaryopoiesis/thrombopoiesis alterations in viral infections.…”
Section: Discussionmentioning
confidence: 99%
“…PaO 2 /FiO 2 ratio doubled from about 100 to 200 mmHg (P<0.001); respiratory rate decreased from 28 [22-32] to 24 [20][21][22][23][24][25][26][27][28][29] breaths per minute, P<0.001). CPAP failure was independently associated with CRP, time to oxygen mask failure, age, PaO 2 /FiO 2 during CPAP, number of comorbidities.…”
mentioning
confidence: 99%